Women in front of the mirror. An approach to the problems of feminine beauty from the territory (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This article describes a university extension experience intended to problematize the relationship between women and beauty in a gender perspective. Such experience was conducted in the northern district of the city of Rosario (province of Santa Fe), in 2023. It consisted of the design and realization of a workshop in which 28 women participated in order to discuss conceptions, violence, and practices linked to beauty in our culture. In this presentation, we present descriptive notes on the experience, along with theoretical reflections we studied, to organize both the approach and the discussion during work on the territory.
Keywords: women; beauty; gender; intersectionality